Business and Product Legality Assistance In Efforts to Improve Branding Quality Jamur Paimo Farm Production House in Ngadirejo Village: Pendampingan Legalitas Usaha dan Produk Dalam Upaya Peningkatan Kualitas Branding Rumah Produksi Jamur Paimo Farm di Kelurahan Ngadirejo - Siti Nurhaliza; Rusdi Hidayat Nugroho (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
MSMEs play an important role in economic growth which has a direct impact on regional economic development. In Ngadirejo Village, Kepanjenkidul District, Blitar City, there is the UMKM